Composting of food and yard wastes by locally isolated fungal strains - Adebayo, Opatokun; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Salihu, Aliyu; Abass, Alade; Dasalo Ruqayyah, Tijani Iyabo (Academic Journals, 2011)
Four lignocellulolytic fungi isolates, Phanerochaete chrysosporium PC-13 (PC2094), Lentinus tigrinus M609RQY, Aspergillus niger and Penicillium spp. were used as inocula in source separated organics (food and yard trimmings) from solid waste (SW) to produce biofertilizer and stabilize waste constituents. The results show that composting with sequential pure culture accelerates substrates decomposition and reduce bulk volume. The initial moisture content was 64%, and the percentage C/N ratio ranged between 8.60 and 18.20%, while the produced compost C/N ratio was <25%, indicating its viability for large scale production since the acceptable C/N ratio for efficient compost is >12%. The 74% total organic matter (TOM), 7.2 pH and 132% germination index (GI) further showed the potentials of the produced compost. Based on this, food waste (FW) and yard trimmings (YT) showed an economic potential for sustainable production of compost using low technology.